Transcriptomic and proteomic analyses of Weissella koreensis isolated from kimchi with different growth-limiting temperatures - Hye In Ko; So-Rim Kim; Moeun Lee; Chae-Rim Jeong; Nuri Na; Jong-Bang Eun; Tae-Woon Kim (Food Research International, 2026)

Leuconostoc mesenteroides TH-ST373 Cell-Free Supernatant Against Multidrug-Resistant Escherichia coli - Gyeong-Seon Yi; Thi Minh Nguyen Trang; Jae-Woo Kim; Jin-woo Choi; Ye-Rim Choi; So-Hee Chun; Qiwen Zheng; Tae-Hoo Yi (Probiotics and Antimicrobial Proteins, 2026)

TDOF PID Controller for Enhanced Disturbance Rejection with MS-Constraints for Speed Control of Marine Diesel Engine - Gun-Baek So; Gang-Gyoo Jin; Chan-Ha Lee; Hye-Rim So; Dae-Jeong Kim; Jong-Kap Ahn (Journal of Marine Science and Engineering, 2024)
This study proposes a two-degree-of-freedom PID controller design and tuning method based on a simple pole placement approach to enhance servo and regulatory performance while ensuring the stability of diesel engines. In the modeling of the control target, the actuator is analytically modeled. In contrast, the type of model for the diesel engine is derived analytically, and its parameter estimation uses operational data from naval ships. The proposed controller consists of a PID controller to improve regulatory performance and a set-point filter to enhance servo response. PID controller parameters consist of the parameters of the controlled plant model and a single tuning variable. At the same time, the set-point filter comprises the controller parameters and a single weighting factor. To ensure the robust stability of the controller, the controller parameters are tuned based on the maximum sensitivity. To verify the effectiveness of this study, simulations for the speed control of a diesel engine with inherent nonlinearity were conducted under three scenarios. Performance was quantitatively analyzed using the integral of time-weighted absolute error, 2% settling time, 2% recovery time, specified maximum sensitivity, and maximum peak response value, and was compared with Skogestad’s IMC and Lee’s IMC. Based on evaluation indices, the proposed controller demonstrated superior performance in both servo and regulatory responses compared to the two existing control techniques while ensuring stability.

Monthly climate variation over Korea in relation to the two types of ENSO evolution - Sae‐Rim Yeo; Sang‐Wook Yeh; Yoojin Kim; So‐Young Yim (International Journal of Climatology, 2018)
This study documents monthly temperature and precipitation anomalies over Korea during the different phases of El Niño‐Southern Oscillation (ENSO) for the two types of ENSO evolution. The evolution process of ENSO can be classified into two groups based on whether El Niño turns into La Niña in the subsequent year. The first group involves the transition process from El Niño to La Niña, while the second group shows the prolonged El Niño or neutral conditions after the mature phase of El Niño. Because the mid‐latitude atmospheric responses as well as the equatorial heating anomalies for the two groups of ENSO are different each other, the ENSO‐related climate variation over Korea are investigated separately for the two ENSO evolution groups. In particular, this study focuses on the entire monthly evolution of the temperature and precipitation over Korea during the different phases of ENSO. The statistically robust signals can be found in several particular months, which provides statistical basis for predicting monthly climate over Korea. In addition to the observational data analyses, we further investigate the forecast skill of the Asia‐Pacific Economic Cooperation Climate Center (APCC) Multi‐Model Ensemble (MME) in simulating two groups of ENSO evolution and their impacts on Korean climate. The result shows that the MME reasonably predicts the two different evolution of ENSO as in observation but their prediction skills for the ENSO‐related Korean climate are diverse, which largely depends on the phase of ENSO.

Diagnostic usefulness of the GenoType MTBDR plus assay for detecting drug-resistant tuberculosis using AFB smear-negative specimens with positive TB-PCR result - Young Seok Lee; Hye-Rim Kang; Si-Hyeong Lee; Yunmi Kim; Mi-Yeong Kim; Jeong Hwan Shin; Jae Young Moon; Hyun-Kyung Lee; So Young Park; Eun-Kyung Mo; Yong Bum Park; Soo-Yoon Moon; et al. (Infectious Diseases, 2016)

Characterization of a hybrid bone substitute composed of polylactic acid tetrapod chips and hydroxyapatite powder - So Hee Park; Sung-Hee Park; Dae Sung Park; Yun Gyeong Kang; Ji Won Shin; Hyung Keun Kim; Taek Rim Yoon; Jung-Woog Shin (Tissue Engineering and Regenerative Medicine, 2013)

Dual knockdown of p65 and p50 subunits of NF-kappaB by siRNA inhibits the induction of inflammatory cytokines and significantly enhance apoptosis in human primary synoviocytes treated with tumor necrosis factor-alpha - Ui Jin Lee; So-Rim Choung; K. V. Bhanu Prakash; Eun-Ju Lee; Mi Young Lee; Young Joo Kim; Chang-Whan Han; Young-Chul Choi (Molecular Biology Reports, 2008)